Improvement of Peat Water Quality Using a Mix of Lime, Bentonite, and PAC as Living Media for Goldfish (Cyprinus carpio) - Ramos Gunawan; Hasbi Hasbi; Eko Purwanto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
Abstract The people of Pasiran Village have utilized peat water for commercial activities in the form of aquaculture. Based on water quality, peat waters are not suitable for aquaculture because of their high color intensity, a high degree of acidity, high organic matter content, low concentrations of suspended particles, and ions. For this reason, it is necessary to make efforts to improve the quality of peat waters. The aim of this is to study to know the effect of a mixture of lime, bentonite, and PAC on improving the quality of peat water used as a living medium for carp (Cyprinus carpio) and find the best dose of all treatments. The method used in this research is an experimental method with a completely randomized design (CRD) with one factor, and 5 levels, with 3 replications. The results showed that the mixture of lime, bentonite, and PAC on the improvement of peat water quality had a significant effect. The best dose to improve the quality of peat water is at the level of 0,5 g of lime, 0,51 g of bentonite and 0,49 PAC, and the survival test value of goldfish (Cyprinus carpio), it show that P1 treatment gives the best result, reaches 93%.Keywords: Pentwater, Lime, PAC, Bentonite, Goldfish (Cyprinus carpio)